2018
DOI: 10.1097/brs.0000000000002503
|View full text |Cite
|
Sign up to set email alerts
|

Predictability of Supine Radiographs for Determining In-Brace Correction for Adolescent Idiopathic Scoliosis

Abstract: 3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
56
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(57 citation statements)
references
References 33 publications
1
56
0
Order By: Relevance
“…Hence, the results of this study do not indicate the duration of brace wear required. In addition, curve flexibility has been shown to greatly influence the outcomes of bracing and surgery [ 32 33 34 35 ]. This aspect of bracing, as well as the varied responses of different curve patterns, is beyond the intent of this study and should be addressed in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, the results of this study do not indicate the duration of brace wear required. In addition, curve flexibility has been shown to greatly influence the outcomes of bracing and surgery [ 32 33 34 35 ]. This aspect of bracing, as well as the varied responses of different curve patterns, is beyond the intent of this study and should be addressed in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…It is also important to note the potential effects of anesthesia on curve magnitude. Similar to human studies where effects of posture may lead to changes in spinal alignment and severity (7,25), variations in muscle tone may lead to measurement variability. The mean RSD was 125.3% which indicated a big variation and this serves as a guide to the degree of variability that exists in every radiographic measurement.…”
Section: Discussionmentioning
confidence: 99%
“…The negative correlation between CA and IBC has been confirmed in our study and previous studies. Studies also revealed that sagittal or coronal imbalance of the spine can decrease IBC and suggested that IS is a complex 3-dimensional deformity of the spine and that sagittal imbalance can affect the curve correction in the coronal plane [7,11]. Georges and Pierre et al made the same conclusion that pelvis morphology and standing balance parameters are correlated with CA, they suggested that IS is not only a question of trunk morphology distortion by itself, but is also related to pelvis asymmetrical bone growth and standing neuromuscular imbalance [12].…”
Section: Discussionmentioning
confidence: 99%
“…IBC refers to the percentage of improvement in the curve size at the initial brace prescription. Given the significance of IBC, some studies have been performed to find related imaging parameters to predict the IBC [7]. Self-parameters of IS, such as primary Cobb angle and coronal deformity angular ratio, was found to correlate with IBC [8].…”
Section: Introductionmentioning
confidence: 99%